Human umbilical cord mesenchymal stem cells and exosomes: bioactive ways of tissue injury repair - Yin, Siqi (Am J Transl Res, 2019)
Mesenchymal stem cells (MSCs) can be recruited to damaged tissues directly for regeneration. Exosomes, acting as an important ingredient of MSCs-involved intercellular communication through paracrine actions, also play significant roles in tissue damage repair and have a prospect of potential clinical application. It is generally recognized that MSC-derived exosomes (MSC-exosomes) enhance tissue regeneration and repair through reducing inflammatory responses, promoting proliferation, inhibiting apoptosis and facilitating angiogenesis. This review summarizes the positive effects of human umbilical cord mesenchymal stem cells (hucMSCs) and hucMSC-derived exosomes (hucMSC-exosomes) on tissue damage and the specific mechanisms of repair action.